Feasibility and impact of near-point-of-care integrated tuberculosis/HIV testing in Malawi and Zimbabwe. (1st December 2021) - Wang, Melody; Boeke, Caroline E.; Rioja, Maria Rosezoil; Maparo, Tatenda; Banda, Clement; Chavula, Chancy; Gunda, Andrews; Isaac, Jean; Mangwiro, Alexio; Mangwendeza, Phibeon Munyaradzi; Mtaula, Jonathan; Mwase, Christopher; et al.
Abstract : Objectives: Near-point-of-care (POC) testing for early infant diagnosis (EID) and viral load expedites clinical action and improves outcomes but requires capital investment. We assessed whether excess capacity on existing near-POC devices used for TB diagnosis could be leveraged to increase near-POC HIV molecular testing, termed integrated testing, without compromising TB services. Design: Preimplementation/postimplementation studies in 10 health facilities in Malawi and 8 in Zimbabwe. Methods: Timeliness of EID and viral load test results and clinical action were compared between centralized and near-POC testing using Somers' D tests (continuous indicators) and risk ratios (RR, binary indicators); TB testing/treatment rates and timeliness were analyzed preintegration/postintegration. Results: With integration, average device utilization increased but did not exceed 55%. Despite the addition of HIV testing, TB test volumes, timeliness, and treatment initiations were maintained. Although few HIV-positive infants were identified, near-POC EID testing improved treatment initiation within 1 month by 57% compared with centralized EID [Malawi RR: 1.57, 95% confidence interval (CI) 0.98–2.52], and near-POC viral load testing significantly increased the proportion of patients with elevated viral load receiving clinical action within 1 month (Zimbabwe RR: 5.26, 95% CI 3.38–8.20; Malawi RR: 3.90, 95% CI 2.58–5.91). Conclusion: Integrating TB/HIV testing using existing multidisease platforms is feasible and enables increased access to rapid diagnostics without disrupting existing TB services. Our results serve as an example of a novel, efficient implementation model that can increase access to critical testing services across disease silos and should be considered for additional clinical applications. Abstract : Supplemental Digital Content is available in the text